LncRNA GTF3C1 promotes diabetic corneal wound healing by regulating GABARAP and PTEN to augment autophagy - Danling Liao; Wenqu Chen; Yuyang Deng; Shijia Wei; Li Wang; Jianzhang Hu (Eye and Vision)
Abstract Background Diabetic keratopathy (DK) is a common ocular complication of diabetes, with its progression closely linked to autophagy regulation. This study aims to explore the role of long non-coding RNAs (lncRNAs) in modulating autophagy during diabetic pathogenesis, focusing on lncRNA general transcription factor IIIC subunit 1 (GTF3C1) and its potential as a therapeutic target for diabetic corneal neuropathy (DCN). Methods High-throughput sequencing identified dysregulated lncRNAs in the trigeminal ganglia of diabetic mice. Functional validation included mechanistic studies on lncRNA GTF3C1, miR-542-3p, and autophagy-related targets. Autophagy activity, corneal nerve density, and epithelial healing were quantified using quantitative real-time polymerase chain reaction (qRT-PCR), immunofluorescence, and histology in diabetic models. Results lncRNA GTF3C1 was significantly downregulated in diabetic trigeminal ganglion (TG). It functioned as a molecular sponge for miR-542-3p, alleviating its repression on GABA type A receptor-associated protein (GABARAP) and phosphatase and tensin homolog (PTEN), thereby enhancing autophagy activity. This process promoted corneal nerve fiber regeneration and epithelial wound healing in diabetic mice. Conclusions Our findings highlight lncRNA GTF3C1 as a critical regulator of autophagy in diabetic corneal nerves, offering a potential diagnostic and therapeutic target for DCN. This study provides molecular insights into the pathogenesis of DCN and lays the groundwork for future clinical strategies.